A Study on the Employability of Bachelor of Arts Graduates from Tribhuvan University in Makawanpur District - Timalsina, Keshab Prasad; Humagain, Sumargi (Community College Research Journal, 2025)
This study analyzes the skills gaps in Bachelor of Arts (BA) students from Tribhuvan University, Nepal, concerning employability from the perspective of stakeholders such as NGOs, industries, schools, local government, and students. Drawing on qualitative narrative analysis of data gathered from needs assessment at Makwanpur Multiple Campus (2025), the study outlines five major gaps in the humanities curriculum: deficiency in professional writing and communication skills, technology and digital skills, experiential learning andpractical training, interactive and creative teaching competencies, and market and community need responses. Stakeholder anecdotes, such as an NGO coordinator’s frustration with graduates’ failure to prepare reports and a principal’s frustration with inefficient pedagogical practices, are complemented by graduate case studies, such as a sociology graduate who became a juice vendor and a rural development graduate who is a cashier. Grounded in Human Capital Theory and Employability Theory, the study comes to discover that a theory-driven curriculum reduces graduate’s employability readiness and places training costs on employers. The study proposes curriculum changes like mandatory internships, computer skills classes, and employer participation to enhance employability and make education responsive to Nepal’s socio-economic requirements. The findings further provide an idea of requirement to bridge the incompatibility between academic training and employment market demand within Nepal’s higher education system.